2016
DOI: 10.1177/0333102416636097
|View full text |Cite
|
Sign up to set email alerts
|

Can migraine aura be provoked experimentally? A systematic review of potential methods for the provocation of migraine aura

Abstract: Background The nature of the migraine aura and its role in migraine pathophysiology is incompletely understood. In particular, the mechanisms underlying aura initiation and the causal relation between aura and headache are unknown. The scientific investigation of aura in patients is only possible if aura can be triggered. This paper reviews potential methods for the experimental provocation of migraine aura. Methods We systematically searched PubMed for studies of experimental migraine provocation, including c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 91 publications
0
29
0
Order By: Relevance
“…13,16 This may explain why we were not able to show temporal changes of the BOLD response. First, ideally the patients should be scanned continuously from immediately prior to the initiation of aura symptoms.…”
Section: Methodological Considerationsmentioning
confidence: 86%
See 1 more Smart Citation
“…13,16 This may explain why we were not able to show temporal changes of the BOLD response. First, ideally the patients should be scanned continuously from immediately prior to the initiation of aura symptoms.…”
Section: Methodological Considerationsmentioning
confidence: 86%
“…10,11 One study using BOLD fMRI reported signal changes with several characteristics of CSD during a typical scintillating scotoma in a migraine patient provoked by physical activity. 13 In the present study, we used state of the art high-field BOLD fMRI during visual stimulation combined with retinotopic mapping to investigate migraine patients during various forms of aura symptoms induced by hypoxia, sham hypoxia, or physical exercise with concurrent photostimulation. 13 In the present study, we used state of the art high-field BOLD fMRI during visual stimulation combined with retinotopic mapping to investigate migraine patients during various forms of aura symptoms induced by hypoxia, sham hypoxia, or physical exercise with concurrent photostimulation.…”
mentioning
confidence: 99%
“…Procedures involving damage to the wall of arteries supplying blood to the brain have been reported to induce migraine attacks with aura . Cerebral angiography by direct carotid puncture is a relatively consistent trigger, which induces the patients’ usual aura symptoms in at least 30% of cases .…”
Section: Discussionmentioning
confidence: 99%
“…Studies involving the provocation of migraine attacks without aura in migraine patients using vasoactive substances have provided tremendous insights into the pathophysiology of migraine . A robust method for experimental provocation of migraine aura, however, has not yet been established . Migraine provocation using vasodilating drugs (glyceryl trinitrate, calcitonin‐gene related peptide, and cilostazol) has been attempted in patients suffering from migraine with aura specifically .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of potential methods for the provocation of migraine has been conducted by Lindblad et al in 2016 12. The systematic review has identified studies of experimental migraine aura provocation by administration of sublingual glyceryl trinitrate,13 calcitonin gene-related peptide infusion,14 intravenous injection of insulin,15 visual stimulation,16 chocolate,17 or physical activity 18…”
Section: Discussionmentioning
confidence: 99%